An assessment of the financial reporting practices of some listed Philippine Banks in 2008 - Cayanan, Arthur S. (Philippine Management Review, 2009)
This article shows the results of the assessment of the listed Philippine banks' financial reporting practices as regards their compliance with the generally accepted accounting principles in the Philippines. The results were compared with the findings of the study on the 2003 annual reports of listed Philippine banks.